Trespasser - Doiron, Paul. (New York : Minotaur Books, 2011)
While on patrol, Bowditch receives a call for help. A woman has reportedly struck a deer. When the game warden arrives on the scene, he finds blood in the roadbut both the driver and the deer have vanished.
Maine author.
Keywords: Game wardens -- Fiction; Traffic accidents -- Fiction; Missing persons -- Fiction; Young women -- Crimes against -- Fiction; Lobster fishers -- Fiction; False imprisonment -- Fiction; Maine -- Fiction